THE RELATIONSHIP OF BODY IMAGE WITH EATING PATTERN IN LEVEL 4 STUDENTS DURING THE COVID-19 PANDEMIC AT STIKES SANTA ELISABETH MEDAN - Pomarida Simbolon; Ance Siallagan; Novia Ayu (Jurnal EduHealth, 2022)
Diet is one of the basic needs for humans, during the pandemic, there are changes in eating patterns such as conditions and time, causing a high body image. One of the causes of a high eating pattern is because the quarantine period makes students unable to manage eating schedules and sports activities are rarely done.Method :This study used a correlation research research design with a cross sectional design. Technique sampling techniquePurposive sampling of 108 Level 4 students at STIKes Santa Elisabeth Medan.Results :The results showed thatbody imagelow (54.6%), and high diet (52.8%). Based on the results of the chi-square statistical test, a p-value of 0.001 (p<0.05) was obtained., so that Ha is accepted, it means that there is a relationship between Body Image and Diet for Level 4 Students During the Covid-19 Pandemic Period at STIKes Santa Elisabeth MedanConclusion :Studythis is expected toThe next researcher is to be able to increase knowledge and insight about Body Image with eating patternsso that students are aware of and regulate irregular eating patterns better and consume healthy foods in order to produce a better body image. Respondents are expected to be able to schedule a regular diet with regular exercise activities